Aspek Kerentanan Usaha Ternak Sapi Perah di Kabupaten Malang - Amam Amam; Pradiptya Ayu Harsita (Fakultas Pertanian, Universitas Timor, 2019)
Vulnerability in dairy cattle farming business is a hazard condition (natural or artificial hazards) that can pose a risk of loss in dairy cattle farming business. This research aims to evaluate the impact of the vulnerability aspect of dairy cattle farming business on the farmer institutions and the development of dairy cattle farming business. The research was conducted at the Kelompok Usaha Bersama (KUB) Tirtasari Kresna Gemilang, Malang District, East Java. Respondents are all farmers who are members of the KUB Tirtasari Kresna Gemilang, which is 174 people. Data was analyzed by the SEM (Structural Equation Model) method with the SmartPLS application. The results showed that the vulnerability aspects negatively affected on the farmer institutional and the development of dairy cattle farming business, and the farmer institutional positively effected on the development of dairy cattle farming business. The conclusion of this study is that livestock business development is influenced by vulnerability aspect and institutional aspects of dairy cattle farmers. Suggestions that must be considered by farmers and institutional dairy farmers are vulnerability aspects which include fluctuations in the selling price of fresh milk, government policies, group policies, and the morality of farmers in the group.